(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
The Merchandising Management System is developed to address the inefficiencies in the manual administrative operations of Great Wall Arts Company, which previously relied on Excel sheets, Google Drive, and physical documentation. This system aims to centralize merchandise management and automate administrative tasks through artificial intelligence (AI), particularly in areas such as real-time report generation and data analysis. The project adopted a structured development methodology, starting with stakeholder consultations to gather system requirements and analyze existing workflows. The system was designed with core modules such as document management, secure user authentication with role-based access control, and AI-driven reporting. Web-based technologies and a secure database infrastructure were used to ensure functionality, scalability, and security. AI features were integrated to automate data collection and reporting processes. The system successfully replaced fragmented and manual workflows with a unified and secure digital platform. AI-driven real-time reporting delivered timely and accurate insights, enhancing data-driven decision-making and reducing the margin of human error. Role-based access control improved information security, while centralized document management increased operational efficiency across departments. The implementation of the system streamlined the company’s administrative processes, reducing dependency on outdated tools and enhancing productivity. By automating report generation and securing sensitive data, the system positioned the organization for future scalability and innovation. The integration of AI functions not only improved operational accuracy but also laid the foundation for long-term digital transformation.